Alternatives in Jewish bioethics - Zohar, Noʻam (State University of New York Press, 1997)
A dialogue between contemporary, Western moral philosophy and the tradition of Legal/Moral Descourse (Halakha).
Keywords: Medicine -- Religious aspects -- Judaism.; Bioethics.; Medical laws and legislation (Jewish law); Jewish ethics.; Humanities.; Sociology.; Art.; Suicide.; Culture.; Hospice care.; Terminal care.; Health services accessibility.; Health planning.; Medical personnel.; Reproductive technology.; Social psychology.; Economics.; Death.; Methodology.; Medical care.; Social sciences.; Social problems.; Ethnology.; Therapeutics.; Anthropology.; National health services.; Public health.; Diseases.; Human behavior.; Theology.; Euthanasia.; Cultural pluralism.; Do-not-resuscitate orders.; Assisted suicide.; Humanism.; Religion.; Human reproductive technology.; Philosophy.; Judaism.; Dead.; Social values.; Humanities; Sociology; Art; Suicide; Culture; Terminal Care; Health Services Accessibility; Health Planning; Health Occupations; Epidemiologic Research Design; Reproductive Techniques; Psychology, Social; Health Care Quality, Access, and Evaluation; Withholding Treatment; Economics; Homicide; Death; Research Design; Methods; Health Care Evaluation Mechanisms; Patient Care; Epidemiologic Methods; Social Sciences; Investigative Techniques; Health Care Economics and Organizations; Behavior and Behavior Mechanisms; Disciplines and Occupations; Social Problems; Self-Injurious Behavior; Anthropology, Cultural; Therapeutics; Delivery of Health Care; Pathologic Processes; Anthropology; Psychiatry and Psychology; Health Services; Quality of Health Care; Anthropology, Education, Sociology and Social Phenomena; Behavioral Symptoms; Analytical, Diagnostic and Therapeutic Techniques and Equipment; Public Health; Pathological Conditions, Signs and Symptoms; Disease; Health Care Facilities, Manpower, and Services; Behavior; Environment and Public Health; Bioethical Issues; Human Body; Theology; Euthanasia; Random Allocation; Euthanasia, Active, Voluntary; Cultural Diversity; Euthanasia, Active; Euthanasia, Passive; Medicine; Suicide, Assisted; Ethics; Health Care Rationing